Study of the genetic biodiversity of some soybean cultivars with different rust resistant abilities - Phuong Lien, Tran Thi; Muoi, Le Thi; Long, Tran Dinh (Academia Journal of Biology, 2014)
The soybean cultivars G1, G2, G3, G4, G7, G8, G9, G10 and DT2000 were grown and tested for rust resistance. DNA isolated from the young leaves of these cultivars was also studied for the genetic diversity using 12 SSR (simple sequence repeats) markers. The results showed the polymorphism between these cultivars. The genetic diversity index (H) values ranged from 0.1975 for Satt557 to 0.7655 for Satt373. An average of 3.8 alleles produced by SSR loci and a mean gene diversity of 0.6161 were obtained. The genetic distance data revealed that there were two cultivar groups. Three cultivars G1, G2 and G3, which were susceptible to the rust, were in the first group. The second group consisted of six other cultivars G4, G7, G8, G9, G10 and DT2000. The second group was divided into two branches, based on their susceptibility to the rust infection. In the first branch were two varieties G8 and G9, which were moderately infected by the rust and the second branch consisted of four varieties G4, DT2000, G7 and G10, which were highly resistant to the rust. According to the results of the investigation using fungal race provided by the Legume Research and Development Center, there were three susceptible cultivars G1, G2 and G3, with a disease index of 90 to 95% and three high resistant cultivars G4, G7 and G10, with a disease index of 10 to 15%. All of the ten SSR markers (Satt042, Satt146, Satt175, Satt173, Satt557, Satt489, Satt373, Satt150, Satt009 and Satt431) gave out polymorphism at different levels between the first and the second groups. This study has provided new data that would be useful for the selection of parents with different rust resistance abilities and high diversity of the SSR markers that were linked to the rust resistance characteristic.